PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA WATTPAD TERHADAP KETERAMPILAN MENULIS TEKS CERPEN PADA SISWA KELAS IX SMP PGRI CIBEUREUM - Lestari, Dinda Ayu; Nurhayati, Enung; Lestari, Riana Dwi (IKIP Siliwangi, 2025)
This article describes the results of research on the application of the Problem Based Learning model assisted by Wattpad media. This research was motivated by the lack of interest in reading in class IX students so that their writing abilities were quite low. The use of technology is rarely used in the learning process, there needs to be updates in the media used. The learning model used does not vary, making learning outcomes less than optimal. The aim of this research is to determine the application of the Problem Based Learning model assisted by Wattpad media on short story text writing skills in class IX students. This research method is quasi-experimental, the research design used is one group pretest - posttest design. The population in this study were class IX students at PGRI Cibeureum Middle School for the 2023/2024 academic year, consisting of three classes with a total of 85 students. The sample in this research consisted of 25 students. The average pretest score was 60.23 and posttest was 83.28. This increase was strengthened by the results of the T-test, which obtained a value of 0.000 < 0.05, so it can be concluded that there was an increase in students' short story text writing skills after using the Problem Based Learning model. Thus, the application of the Problem Based Learning learning model assisted by Wattpad media can improve the short story writing abilities of class XI students at PGRI Cibeureum Middle School.